Evolutionary biogeography and tectonic history of the ghost moth families Hepialidae, Mnesarchaeidae, and Palaeosetidae in the Southwest Pacific (Lepidoptera: Exoporia) - Grehan, John R.; Mielke, Carlos G.c. (Zootaxa, 2018)
The biogeographic history of Exoporia (Lepidoptera) in the Southwest Pacific is reconstructed for genera and species that show distributional boundaries corresponding to tectonic structures in the region. Correlations with tectonic formations of Mesozoic origin such as the Whitsunday Volcanic Province and Otway-Bass-Gippsland Basin system in Australia, the Vitiaz Fracture Zone in northern Melanesia, and the Western Province-Eastern Province boundary, Waitaki Fault Zone, and Waihemo Fault Zone of New Zealand are presented as evidence of an East Gondwana origin for genera and species before the geological separation of Australia and New Zealand. The correlated boundaries also suggest that many extant species retain at least parts of their original East Gondwana distribution ranges. The presence of Exoporia on the northern Melanesian Arc, New Caledonia, and New Zealand is attributed to the tectonic isolation of these areas when East Gondwana expanded into the Pacific following retreat of the Pacific Plate subduction zone. Local endemism of Mnesarchaeidae in New Zealand is interpreted as the result of an original vicariance from a widespread ancestor (‘Exoporia’) resulting in two allopatric descendants —a narrowly distributed Mnesarchoidea and a widely distributed Hepialoidea. The current overlap of these two groups in New Zealand is explained as the result of subsequent range expansion by the Hepialoidea prior to geological fragmentation of East Gondwana. The potential impact of Cretaceous geography on modern distributions is also considered for Exoporia in southern Africa and northern America. Along with lateral displacement of Exoporia, tectonic processes also contributed to the origin of high elevation endemics through a process of passive tectonic uplift.